Statin therapy and the development of cerebral amyloid angiopathy: a rodent in vivo approach - Reuter, Björn; Grudzenski-Theis, Saskia; Schad, Lothar R.; Hennerici, Michael G.; Fatar, Marc (International journal of molecular sciences, 2016)
Background: Cerebral amyloid angiopathy (CAA) is characterized by vascular deposition of amyloid β (Aβ) with a higher incidence of cerebral microbleeds (cMBs) and spontaneous hemorrhage. Since statins are known for their benefit in vascular disease we tested for the effect on CAA. Methods: APP23-transgenic mice received atorvastatin-supplemented food starting at the age of eight months (n = 13), 12 months (n = 7), and 16 months (n = 6), respectively. Controls (n = 16) received standard food only. At 24 months of age cMBs were determined with T2*-weighted 9.4T magnetic resonance imaging and graded by size. Results: Control mice displayed an average of 35 ± 18.5 cMBs (mean ± standard deviation), compared to 29.3 ± 9.8 in mice with eight months (p = 0.49), 24.9 ± 21.3 with 12 months (p = 0.26), and 27.8 ± 15.4 with 16 months of atorvastatin treatment (p = 0.27). In combined analysis treated mice showed lower absolute numbers (27.4 ± 15.6, p = 0.16) compared to controls and also after adjustment for cMB size (p = 0.13). Conclusion: Despite to a non-significant trend towards fewer cMBs our results failed to provide evidence for beneficial effects of long-term atorvastatin treatment in the APP23-transgenic mouse model of CAA. A higher risk for bleeding complications was not observed.
Gesehen am 17.01.2019